Educational work as a prophetic process of liberation: Paulo Freire's pedagogy in the light of fundamental challenges of global society - Oesselmann, Dirk (2022)
This article reads the educator Paulo Freire from the perspective of the current challenges of a globalised society. The starting point is the demand for a "great transformation" that leads to a changed self-understanding of individuals as well as to a new kind of personal and structural coexistence. In Freire's liberation pedagogy, the aspects that herald the new and thus underpin transformation processes are taken up from this perspective. The author identifies traces of a search for what constitutes and fundamentally sustains human beings - the central topic of religions and spirituality.